2000
DOI: 10.1002/1097-4598(200009)23:9<1335::aid-mus3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Postcontraction depression of reciprocal inhibition in human forearm muscles

Abstract: We tested whether a preceding muscle contraction changes reciprocal inhibition (RI) between forearm antagonists. RI was studied in 14 healthy subjects by assessing changes in the H reflex (evoked by median‐nerve stimulation) in forearm flexor muscles after conditioning radial‐nerve stimulation at 0‐ and 20‐ms intervals. The maximum sizes of the M wave (Mmax) and H reflex (Hmax) were also measured. After a long‐lasting maximum voluntary handgrip contraction (mean ± SEM: 3.9 ± 0.6 min) of ipsilateral forearm mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The possibility that motor fatigue acts on dystonia in the same way as botulinum toxin is unlikely because whereas botulinum toxin decreases the size of the maximum electrically elicited muscle response (M‐wave) in forearm muscle,9 the same motor task we used in this study fails to change the M‐wave size 5. Changes at spinal level seem equally improbable because muscle fatigue reduces reciprocal inhibition,5 a process that is already abnormal in limb dystonia 8, 9. Hence, muscle fatigue should worsen motor performance in patients with dystonia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The possibility that motor fatigue acts on dystonia in the same way as botulinum toxin is unlikely because whereas botulinum toxin decreases the size of the maximum electrically elicited muscle response (M‐wave) in forearm muscle,9 the same motor task we used in this study fails to change the M‐wave size 5. Changes at spinal level seem equally improbable because muscle fatigue reduces reciprocal inhibition,5 a process that is already abnormal in limb dystonia 8, 9. Hence, muscle fatigue should worsen motor performance in patients with dystonia.…”
Section: Discussionmentioning
confidence: 97%
“…Spinal motoneuronal behavior during fatigue is modulated by various factors (from supraspinal commands to presynaptic modulation); all of them decrease the motor–neuronal output. Similarly, a maximal muscle contraction depresses the excitability of inhibitory spinal interneurons controlling reciprocal inhibition 5. Finally, fatigue reduces the motor cortex threshold for inhibitory and excitatory processes 1.…”
Section: Discussionmentioning
confidence: 99%
“…107 Loss of reciprocal inhibition (the normal inhibition of antagonist muscles during a movement) in the arms of patients with writer's cramp could be consistent with a loss of inhibition at a spinal level because this reflex depends on the activity of the agonist muscle Ia sensory afferents. 108,109 Long-lasting voluntary handgrip in healthy subjects reduces reciprocal inhibition, 110 suggesting that excessive motor activity that occurs in task-specific dystonias could act in the same manner.…”
Section: Loss Of Inhibitionmentioning
confidence: 99%
“…This accounts for a characteristic feature of dystonia, namely co-contraction, in which both agonist and antagonist muscles contract together, interfering with reciprocal activation of the limb muscles in writing. A series of experiments performed by Priori et al 14 revealed that a similar reduction of reciprocal inhibition occurs after a long-lasting maximal voluntary handgrip in normal subjects. As they noted, in our daily experience, heavy use of pen-writing sometimes incapacitates the hand by co-contraction of the forearm flexors and extensors.…”
mentioning
confidence: 90%